Prevalence and factors associated with suicide among medical professionals in low/middle-income countries: a systematic review protocol - Rukundo, Godfrey Zari; Byakwaga, Helen; Kinengyere, Alison; Bapolisi, Achille Mwira; Betancourt, Miriela; Akena, Dickens (BMJ open, 2019)
Introduction: A number of studies in low/middle-income countries (LMICs) have reported varying prevalence of suicide among medical professionals with low rates. This may be because of the methods used in suicide assessment and the stigma associated with it. For this study, the prevalence of suicidal ideation, attempt and completed suicide, as well as the factors associated with suicidality and methods used during suicidal acts, will be documented. Methods and analysis: Studies published in peer reviewed journals in which the prevalence and factors associated with suicidal ideation, attempt and completion among medical professionals in LMICs will be included. The Cochrane Library (CENTRAL), PsychINFO, PubMed and Embase will be systematically searched. We will search for all the papers available in the databases up to March 31 2019. Methodological quality of the articles will be assessed using the quality in prognostic studies tool. The risk of bias of the articles will be assessed using Cochrane risk of bias assessment tool for non-randomized studies. In the event of no statistical heterogeneity, a meta-analysis of the findings will be conducted. Ethics and dissemination: Ethical permission will not be required since this work does not involve the use of participant data that can be used to identify individuals. Findings from this study will be available for clinicians and other medical professionals, scientists and policy makers. On request, a data set of the study can be provided.
Keywords: Suicide; Medical professionals; Low/middle-income; Stigma associated; Suicidal ideation